2011
DOI: 10.1093/nar/gkr1212
|View full text |Cite
|
Sign up to set email alerts
|

A central fragment of ribosomal protein S26 containing the eukaryote-specific motif YxxPKxYxK is a key component of the ribosomal binding site of mRNA region 5' of the E site codon

Abstract: The eukaryotic ribosomal protein S26e (rpS26e) lacking eubacterial counterparts is a key component of the ribosomal binding site of mRNA region 5′ of the codon positioned at the exit site. Here, we determined the rpS26e oligopeptide neighboring mRNA on the human 80S ribosome using mRNA analogues bearing perfluorophenyl azide-derivatized nucleotides at designed locations. The protein was cross-linked to mRNA analogues in specific ribosomal complexes, in which the derivatized nucleotide was located at positions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…Rps26 is positioned on the solvent side of the 40S platform and is a crucial component of the 40S ribosome-binding site for mRNA (Ben-Shem et al 2011;Sharifulin et al 2012). Available structural data show that the binding site of eIF3 on the 40S subunit overlaps with Rps26 as well as the other Upf1-interacting ribosomal proteins (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Rps26 is positioned on the solvent side of the 40S platform and is a crucial component of the 40S ribosome-binding site for mRNA (Ben-Shem et al 2011;Sharifulin et al 2012). Available structural data show that the binding site of eIF3 on the 40S subunit overlaps with Rps26 as well as the other Upf1-interacting ribosomal proteins (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[79][80][81] The ribosomal protein S26 lacking a eubacterial counterpart, Residue -base contacts (< 5Å distance) observed between 40s ribosomal proteins and the hcV IRes RNa, are listed is a key component of the ribosomal binding site of the mRNA region 5′ of the codon positioned at the exit site. 82 Cross-linking, gel digestion and mass spectroscopy experiments also suggest that IRES interacts with the 40S ribosomal proteins S3, S10, S14, S16, S18 and p40. [29][30][31][32]83 Most of these proteins are found in the vicinity of the IRES RNA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Rp uS3 is known as one of the main components of the mRNA entry site of the ribosome, therefore it has been suggested that cross-linking of mRNA analogs to this protein in the binary complexes takes place at the entry site [25,41]. However, in the ribosomal complexes containing P site bound tRNA cross-linking of the mRNA analogs to rp uS3 might happen in the very mRNA binding site.…”
Section: Peptides Of Rp Us3 Cross-linked To Mrna Analogsmentioning
confidence: 99%